2015
DOI: 10.1038/srep12552
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Phase-Transformation Induced Texture Evolution and Strengthening in Zirconium Metal: Experiment and Modeling

Abstract: We studied the phase-transition induced texture changes and strengthening mechanism for zirconium metal under quasi-hydrostatic compression and uni-axial deformation under confined high pressure using the deformation-DIA (D-DIA) apparatus. It is shown that the experimentally obtained texture for ω-phase Zr can be qualitatively described by combining a subset of orientation variants previously proposed in two different models. The determined flow stress for the high-pressure ω-phase is 0.5–1.2 GPa, more than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…==½1120 (Trinkle et al, 2003(Trinkle et al, , 2005, which has been observed in shock-loaded Zr by TEM (Cerreta et al, 2005). Recently, a synchrotron X-ray study on high-pressureinduced texture evolution in Zr showed that both ORs can occur under high pressure (Yu et al, 2015). In our study, the same two ORs which are reported for and !…”
Section: Figuresupporting
confidence: 83%
See 2 more Smart Citations
“…==½1120 (Trinkle et al, 2003(Trinkle et al, , 2005, which has been observed in shock-loaded Zr by TEM (Cerreta et al, 2005). Recently, a synchrotron X-ray study on high-pressureinduced texture evolution in Zr showed that both ORs can occur under high pressure (Yu et al, 2015). In our study, the same two ORs which are reported for and !…”
Section: Figuresupporting
confidence: 83%
“…4(a). In contrast, in the parent grain which is oriented with [0110] aligned to the normal of the TEM thin foil, the OR follows (1011Þ ZrO == ð0002Þ and ½0111 ZrO ==½1120 , which is the same as another OR that is sometimes reported between -Zr/Ti and !-Zr/Ti (Usikov & Zilbershtein, 1973;Trinkle et al, 2003;Yu et al, 2015), shown in the pole figure in Fig. 4(b).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The relatively low hardness, typically below the value of 5 GPa, of traditional magnetic materials inevitably impede the application of traditional magnetic materials in harsh conditions91011121314. To strengthen the mechanical properties of ferromagnetic materials, fabricating composite, ageing process, doping and controlling microstructure have been attempted to enhance mechanical properties789151617. However, the mechanical properties of ferromagnetic materials still fall far short the requirements of industrial applications18.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Their applicability is limited by the hcp (a)-simple hexagonal (x) phase transformation under high hydrostatic pressure. [4][5][6][7][8][9] The appearance of the x phase can strengthen the metal, 10,11 while it also greatly lowers its toughness and ductility. [7][8][9] Extensive research has been undertaken to identify, and possibly modify, the mechanism of the hcp-x phase transformation.…”
mentioning
confidence: 99%